Evaluation of Information Security at the XYZ Foundation Using OWASP Top 10 2021 Framework - Mustafa Kamal; Muhammad Nasrullah; Rully Rosadi; Yuvens Anggito; Roy, Sujan Chandra (Journal of Advances in Information and Industrial Technology, 2024)
More than three billion users use the Internet in various fields, including economic, commercial, cultural, social, and governmental activities. The XYZ Foundation is a non-governmental organization that has more than one hundred thousand donors and its partners also use the Internet for their operations, including online zakat and alms transactions. Increasing the use of online transactions also increases the opportunities for cybercrime to occur. Vulnerability testing is required to observe information security in online zakat and alms transactions in the XYZ foundation. This study uses the top 10 OWASP 2021 vulnerability tests on the online zakat and alms transaction website at the XYZ foundation. The results of this research show that one aspect has a medium risk, one aspect is low, and eight aspects are very low. Based on these results, the weak aspects of online zakat and alms transactions in the XYZ foundation must be immediately improved.